Study on Conditions for Carboxymethyl Cellulose Synthesis from Pineapple Leaf Waste and Evaluation of its Thickening Performance - Linh, Nguyen Hai; Linh, Dinh Mai; Hung, Tran Gia; Chau, Nguyen Thi Minh; Thu, Ngo Hong Anh; Son, Nguyen Thi; Giang, Nguyen Truong; Mai, Phan Thi Tuyet (VNU Journal of Science: Natural Sciences and Technology, 2023)
Pineapple leaf waste, with its high cellulose content, can serve as alternative starting material for the production of carboxymethyl cellulose (CMC). In this study, cellulose was  extracted from pineapple leaf waste by 0.5 M NaOH at 90 o C for 2 h and 0.5 M HNO 3 at 90 o C for 2 hour. The obtained cellulose, with average diameters of 3-7 μm, was converted to carboxymethyl cellulose (CMC) by esterification. Preparation of CMC was investigated by varying two factors, namely, sodium hydroxide (NaOH) dosage and monochloroacetic acid (MCA) dosage. The cellulose was soaked in a solution mixture of ethanol and NaOH for 2 h at room temperature. It was then reacted with chloroacetic acid (MCA) at 60 o C for 2 hour. The optimum conditions for carboxymethylation were found to be 0.70 g of MCA/g cellulose, 0.75 g NaOH/g cellulose. The obtained CMC had a high degree of substitution (DS) of 1.0 with the CMC yield of 150%. The obtained CMC were characterized by FTIR spectroscopy, SEM images and XRD diffractions. Moreover, the thickerning performance of the obtained CMC was also determined.